ARTIFICIAL INTELLIGENCE IN FINANCIAL SERVICES: A COMPREHENSIVE ANALYSIS OF TRANSFORMATIVE TECHNOLOGIES AND THEIR IMPACT ON MODERN BANKING - Panneer Selvam Viswanathan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The integration of artificial intelligence (AI) technologies in financial services is fundamentally transforming traditional banking and finance paradigms, creating unprecedented opportunities while presenting novel challenges. This comprehensive article examines the multifaceted applications of AI across the financial sector, focusing on key areas, including algorithmic trading, fraud detection, personalized advisory services, risk assessment, and regulatory compliance. Through systematic analysis of current implementations, the article reveals how machine learning, natural language processing, and advanced analytics enhance operational efficiency, improve decision-making processes, and revolutionize customer experiences in financial institutions. The article critically evaluates both AI integration's transformative potential and limitations, addressing crucial considerations such as data privacy, algorithmic bias, and regulatory compliance. Additionally, the article explores emerging trends in AI-driven financial services, including blockchain integration, multimodal AI applications, and green finance initiatives. This article provides valuable insights for financial institutions, technology developers, policymakers, and researchers navigating the evolving intersection of artificial intelligence and financial services while contributing to the broader understanding of technological innovation in modern banking.